ROLE OF EMOTIONAL INTELLIGENCE IN ENHANCING CONTEXTUAL PERFORMANCE - Chin, Susan; Yusoff, Rosman (PEOPLE: International Journal of Social Sciences, 2017)
In the light of globalisation and the fast pace business environment, business organisations need to have a powerful source of competitive advantage. The purpose of this study is to examine the role of Emotional Intelligence in enhancing the contextual behaviours among the executives in an organisation. The study used a case study approach to examine the research questions. A total of 110 executives took part in this study. The GENOS Emotional Intelligence questionnaire has been used to record the responses. Based on the regression analysis, it was found that 2 dimensions of Emotional Intelligence had significant relationships with the dimensions of Organisational Citizenship Behaviour. Emotional Intelligence helps to “build” a robust workforce which is able to withstand the forces of the environment. Future studies could include mediating or moderating analysis of Organisational Citizenship.